Developing structural representations: their role in analogical reasoning - Ding, Sharon (1995)
Recent research into the development of analogical reasoning has shown that young children are able to recognise and use relational similarity between situations, provided that they possess the necessary domain knowledge (Goswami, 1992). However, in most of the reported studies, the relational structure of the analogy has been made very salient. Circumstances where the relational structure of a problem has to be represented by the problem-solver themselves could result in differing performance. We do not know whether, or in what circumstances, children can correctly construct a representation of the relevant relational information.